Библейские аллюзии в поэзии Янниса Варвериса - Кожуховская, Ю.В. (Культура народов Причерноморья, 2013)
Настоящая статья посвящена выявлению библейских аллюзий в творчестве Янниса
Варвериса; подобное исследование проводится впервые, что позволяет говорить о научной новизне
работы. В статье обращается внимание на отношение Янниса Варвериса к вопросам веры, а также на
способы реализации его мироощущения в поэтическом творчестве. В данной статье использовались
описательный, сопоставительный методы исследования.
Ключевые слова: новогреческая поэзия, библейские аллюзии, Я.Варверис. Дана стаття присвячена виявленню біблейських алюзій в творчості Янніса Варверіса; таке
дослідження проводиться вперше, що дозволяє говорити про наукову новизну роботи. У статті
звертається увага на ставлення Янніса Варверіса до питань віри, а також на засоби реалізації його
світовідчування в поетичній творчості. Методами дослідження є описовий та порівняльний.
Ключові слова: новогрецька поезія, біблейські алюзії, Я. Варверіс. The article is dedicated to the signification of the biblical allusions in the poetry of Yannis Varveris, a
prominent representative of the Greek literary Generation of the Seventies. The writer’s poetic heritage includes
twelve collections of poems which are extensively being translated all over the world, the fact that defines the
actuality of the article. The topic of faith and religion occupies an important place in the works of Yannis
Varveris and its detailed analysis is needed for better understanding of his poetry. Such a research work hasn’t
been conducted yet, the fact which leads to the scientific novelty of the article. The article draws attention to the
attitude of Yannis Varveris to the subject of faith, to the place of the human being in the universe and to the
methods of realization of his mental outlook in his poetry. Much attention is given to the ways of transformation
of the parables, plots and heroes of the Bible. The article gives a detailed analysis of the Bible allusions on
Jesus' walk on water, Marriage at Cana, the miracle of restoring Lazarus of Bethany to life, on the Bible hero
Salome, as well as the allusion on the paper of John Climacus “The Ladder of Divine Ascent, or Ladder of
Paradise” which in its turn has the Bible allusion. The methods of investigation are descriptive and contrastivecomparative.
Key words: Modern Greek poetry, the biblical allusions, Yannis Varveris.